Analysis of mRNA expression of genes related to fatty acids synthesis in goose fatty liver - Shuxia Xiang; Jing Wang; Chunchun Han; Liang Li; Hui Tang; Jia Lv; Zhixiong Pan; Jiwen Wang (Italian Journal of Animal Science, 2010)
The aim of our study was to evaluate the effect of overfeeding on mRNA expression levels of genes involved in lipogenesis, in order to understand the mechanism of hepatic stea - tosis in the goose. Using Landes geese (Anser anser) and Sichuan White geese (Anser cygnoides) as experimental animals, we quantified the mRNA expression of lipogenic genes, acetyl-CoA carboxylase-α (ACCα) and fatty acid synthase (FAS), and of two transcription factors, sterol regulatory element-binding proteins- 1 (SREBP-1) and carbohydrate responsive element-binding protein (ChREBP) by real-time polymerase chain reaction (RTPCR), and measured the lipid and triglyceride (TG) content in the liver and the plasma level of glucose, insulin and TG. Our results indicated that compared to the control group, the overfeeding induced an increase of the lipid and TG content in the liver and also of the plasma insulin and TG concentration in both breeds. However, the plasma glucose level decreased after overfeeding in the Sichuan White goose, and there was no evident change in the Landes goose. Lastly, the mRNA expression of ACCα, FAS, SREBP-1 and ChREBP in the overfed group was lower than in the control group in both breeds. We concluded that the lipogenesis pathway plays a role in overfeeding- induced hepatic steatosis and that the decreased mRNA level of related genes may be the indicator of hepatic steatosis.